“Shall we dance?”: The art of aerobic dance on improving health-related fitness among overweight females / Patricia Pawa Pitil and Dorathy Baja Sulaiman - Pawa Pitil, Patricia; Baja Sulaiman, Dorathy (2022)
Objective: This study aimed to evaluate the effect of 8-week aerobic dance on body mass index (BMI), body fat percentage and aerobic fitness among overweight female adults (N=32, [body mass index (BMI) ≥ 23 kg/m2, age 18-25 years). The aerobic dance program was conducted three sessions per week for 8 weeks at submaximal intensity. Results: After the 8-week intervention, the aerobic dance group had significantly more changes in BMI, body fat percentage and aerobic fitness than the control group. Conclusion: An 8-week aerobic dance intervention with submaximal intensity can considerably reduce BMI and body fat and improve aerobic fitness among overweight female adults. Good program adherence was attributed to this study.